2020
DOI: 10.1200/jco.2020.38.15_suppl.12010
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric assessment-driven intervention (GAIN) on chemotherapy toxicity in older adults with cancer: A randomized controlled trial.

Abstract: 12010 Background: Geriatric assessment (GA) can predict chemotherapy (chemo) toxicity in older adults (age ≥65) with cancer. However, evidence regarding the effect of GA-driven intervention (GAIN) on the incidence of chemo toxicity has been limited. Therefore, we conducted a randomized controlled trial evaluating the impact of GAIN vs. standard of care (SOC) on chemo toxicity in older adults with cancer. Methods: Patients (pts) age ≥65, diagnosed with a solid malignancy, and starting a new chemo regimen at Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 0 publications
0
62
0
3
Order By: Relevance
“…However, if therapy is used with curative intent, careful consideration should be taken as dose modification could reduce efficacy. Likewise, measures could be initiated to improve the nutritional and functional status of older patients, although the randomized study GAIN (Geriatric assessment-driven intervention) showed that such measures only reduce drug toxicity but not UH or the number of visits to the emergency department [ 22 ]. Supportive care and close monitoring should be established in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, if therapy is used with curative intent, careful consideration should be taken as dose modification could reduce efficacy. Likewise, measures could be initiated to improve the nutritional and functional status of older patients, although the randomized study GAIN (Geriatric assessment-driven intervention) showed that such measures only reduce drug toxicity but not UH or the number of visits to the emergency department [ 22 ]. Supportive care and close monitoring should be established in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although GA‐guided interventions are effective for improving survival and functional status in several scenarios [2], there is a lack of information regarding the effects of GA‐guided care on traditional “hard” oncological outcomes, such as overall survival (OS), treatment toxicity, or quality of life (QoL) [3]. Fortunately, four randomized clinical trials (RCT) presented at the 2020 ASCO Annual Meeting have provided new evidence showing that the implementation of GA‐guided interventions for older adults with cancer can in fact lead to improvements in QoL and decreased treatment toxicity, without compromising survival (Table 1) [ 4–6]. These RCTs represent a giant leap forward for geriatric oncology, because they provide a strong foundation that will allow for GA‐guided interventions to become the standard of care for all older adults with cancer.…”
Section: Figurementioning
confidence: 99%
“…The GAIN RCT studied the effect of a multidisciplinary team (MDT) GA‐guided intervention on the outcomes of patients with solid tumors treated at a single cancer center in southern California [5]. In GAIN, patients aged ≥65 years with solid tumors (any stage) starting a new line of chemotherapy were randomized 2:1 to the MDT GA intervention or to usual oncologist‐guided care.…”
Section: Figurementioning
confidence: 99%
“…On the other hand, a recent study indicates that when the GA is not taken into account for prescribing chemotherapy, 34% of unfit patients are overtreated, which is associated with more grade 3-4 toxicity than those receiving treatment adapted to fragility (42% vs. 31%; p < 0.05) (9). In addition, recently, two randomized clinical trials evaluating the impact of GA vs. standard of care on chemo toxicity in older adults with cancer showed the integration of multidisciplinary GA-driven interventions reduced the incidence of grade 3-5 chemo-related toxicity by 10-20% [37,38].…”
Section: Frailty In Elderly Patients With Metastatic Crcmentioning
confidence: 99%